Intraoperative assessment of reduction and implant placement in acetabular fractures - limitations of 3D-imaging compared to computed tomography - Keil, Holger; Beisemann, Nils; Schnetzke, Marc; Vetter, Sven Y.; Swartman, Benedict; Grützner, Paul Alfred; Franke, Jochen (Journal of orthopaedic surgery and research, 2018)
In acetabular fractures, the assessment of reduction and implant placement has limitations in conventional 2D intraoperative imaging. 3D imaging offers the opportunity to acquire CT-like images and thus to improve the results. However, clinical experience shows that even 3D imaging has limitations, especially regarding artifacts when implants are placed. The purpose of this study was to assess the difference between intraoperative 3D imaging and postoperative CT regarding reduction and implant placement.